2022
DOI: 10.1186/s12887-022-03160-1
|View full text |Cite
|
Sign up to set email alerts
|

Pain points in parents’ interactions with newborn screening systems: a qualitative study

Abstract: Background & Objectives This study aims to explore and elucidate parents’ experience of newborn screening [NBS], with the overarching goal of identifying desiderata for the development of informatics-based educational and health management resources. Methods We conducted four focus groups and four one-on-one qualitative interviews with a total of 35 participants between March and September 2020. Participants were grouped into three types: paren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 39 publications
1
10
0
1
Order By: Relevance
“…The study findings are coherent with those reported in previous studies on UK and US parents receiving a communication of true or false positive ENBS (Beucher et al, 2010; Brockow & Nennstiel, 2019; Buchbinder & Timmermans, 2012; Chudleigh et al, 2016; Collins et al, 2013; Conway et al, 2022; Davis et al, 2006; Deliberazione Giunta Regionale Lombardia, 110 del 14 maggio, 2018; DeLuca et al, 2011, 2012; Dillard et al, 2010; Dixon‐Woods, 2011; Farrell et al, 2020; Gale et al, 2013; Legge 19 agosto, 2016; Ministero della Salute, Decreto 13 ottobre, 2016; Morrison & Clayton, 2011; Salm et al, 2012; Tluczek et al, 2009; Ulph et al, 2017), suggesting that there are some commonalities across countries in the recommendations that can be developed from qualitative studies on ENBS. In particular, information needs, emotional distress linked to the communication of results and the importance of helping parents to navigate the healthcare system and the ENBS programme seem to be central and common topics in the USA as well as in Italy.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The study findings are coherent with those reported in previous studies on UK and US parents receiving a communication of true or false positive ENBS (Beucher et al, 2010; Brockow & Nennstiel, 2019; Buchbinder & Timmermans, 2012; Chudleigh et al, 2016; Collins et al, 2013; Conway et al, 2022; Davis et al, 2006; Deliberazione Giunta Regionale Lombardia, 110 del 14 maggio, 2018; DeLuca et al, 2011, 2012; Dillard et al, 2010; Dixon‐Woods, 2011; Farrell et al, 2020; Gale et al, 2013; Legge 19 agosto, 2016; Ministero della Salute, Decreto 13 ottobre, 2016; Morrison & Clayton, 2011; Salm et al, 2012; Tluczek et al, 2009; Ulph et al, 2017), suggesting that there are some commonalities across countries in the recommendations that can be developed from qualitative studies on ENBS. In particular, information needs, emotional distress linked to the communication of results and the importance of helping parents to navigate the healthcare system and the ENBS programme seem to be central and common topics in the USA as well as in Italy.…”
Section: Discussionsupporting
confidence: 92%
“…Recently, Conway and colleagues (Conway et al, 2022) made a summary of the recommendations available in the literature to improve the quality and effectiveness of communication in the ENBS process (Buchbinder & Timmermans, 2012; Chudleigh et al, 2016; Davis et al, 2006). Nevertheless, these recommendations cannot be generalized to all countries and healthcare settings but needed to be adapted to specific cultures and organizational aspects of the ENBS process.…”
Section: Introductionmentioning
confidence: 99%
“…Prior research of family attitudes towards NBS in Duchenne have indicated that families have historically endorsed the use of NBS, even before treatments for Duchenne were available (Firth & Wilkinson, 1983 ). More generally, research has observed mixed attitudes towards NBS (Conway, Vuong, Hart, Rohrwasser, & Eilbeck, 2022 ). Providing a more detailed understanding of Duchenne diagnostic experiences can inform decision‐makers concerning the value of NBS for Duchenne.…”
Section: Introductionmentioning
confidence: 99%
“…외국의 선행연구에서도 가족에게 정밀검사를 위한 예약의 어려움, 검사 후 최종 결과가 나오기까지 기다리는 시간이 큰 고통인 것으로 보고하고 있다[ 8 , 12 ]. 따라서 이런 부모들의 심리적 요인을 고려하여 재검사, 확진검사 과정을 보다 체계화, 신속화하기 위한 노력이 요구된다[ 30 , 31 ].…”
Section: Discussionunclassified